Low-Dose Lactulose as a Prebiotic for Improved Gut Health and Enhanced Mineral Absorption - Karakan, Tarkan; Tuohy, Kieran Michael; Janssen-van Solingen, Gwendolyn (Frontiers in Nutrition, 2021)
Although medium and high doses of lactulose are used routinely for the treatment of constipation and hepatic encephalopathy, respectively, a wealth of evidence demonstrates that, at low doses, lactulose can also be used as a prebiotic to stimulate the growth of health promoting bacteria in the gastrointestinal tract. Indeed, multiple preclinical and clinical studies have shown that low doses of lactulose enhance the proliferation of health-promoting gut bacteria (e.g., Bifidobacterium and Lactobacillus spp.) and increase the production of beneficial metabolites (e.g., short-chain fatty acids [SCFAs]), while inhibiting the growth of potentially pathogenic bacteria (e.g., certain clostridia). SCFAs produced upon microbial fermentation of lactulose, the most abundant of which is acetate, are likely to contribute to immune regulation, which is important not only within the gut itself, but also systemically and for bone health. Low dose lactulose has also been shown to enhance the absorption of minerals such as calcium and magnesium from the gut, an effect which may have important implications for bone health. This review provides an overview of the preclinical and clinical evidence published to date showing that low dose lactulose stimulates the growth of health-promoting gut bacteria, inhibits the growth of pathogenic bacteria, increases the production of beneficial metabolites, improves mineral absorption and has good overall tolerability. Implications of these data for the use of lactulose as a prebiotic are also discussed.